Tempering the Wrath of RAGE: An Emerging Therapeutic Strategy Against Diabetic Complications, Neurodegeneration and Inflammation - Yan, Shi Fang (2009)
The multi-ligand receptor RAGE (Receptor for Advanced Glycation Endproducts) is emerging as a central mediator in the immune/inflammatory response. Epidemiological evidence accruing in the human suggests upregulation of RAGE’s ligands (AGEs, S100/calgranulins, HMGB1 and amyloid β-peptide and β-sheet fibrils) and the receptor itself at sites of inflammation and in chronic diseases such as diabetes and neurodegeneration. The consequences of ligand-RAGE interaction include upregulation of molecules implicated in inflammatory responses and tissue damage, such as cytokines, adhesion molecules and matrix metalloproteinases. In this review, we discuss the localization of RAGE and its ligand families and the biological impact of this axis in multiple cell types implicated in chronic diseases. Lastly, we consider findings from animal model studies suggesting that although tissue-damaging effects ensue from recruitment of the ligand-RAGE interaction, in distinct settings, adaptive and repair/regeneration outcomes appear to override detrimental effects of RAGE. As RAGE blockade moves further into clinical development, clarifying the biology of RAGE garners ever-increasing importance.